PRECOCIOUS PUBERTY AND PEER RELATIONSHIPS OF PREADOLESCENT GIRLS - Catherine Kawira; Anne Wambugu; Nathan Chiroma, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This article discusses the relationship between precocious puberty and the peer relationships of preadolescent girls in public primary schools in Kiambu County, Kenya. This article is based on a case study of twelve selected public primary schools (representing the 12 constituencies) of Kiambu County, Kenya. The sample population was a total of four hundred and ten pre-teenage girls drawn from eight to twelve-year-old girls, and eight class teachers, who were purposively sampled from twelve randomly selected public primary schools in the study location. This was a mixed study that utilized both quantitative and qualitative data collection methods. The self-rating scale for pubertal maturation and the peer connectedness scale was used to assess for signs of precocious puberty and the quality of peer relationships respectively. In addition, structured interviews and focus group discussions were used to gather additional primary data. The instruments were pilot-tested on a sample of thirty-six respondents who were purposively sampled from three public primary schools in the sample location, and who were omitted from the actual study sample. The quantitative data was analysed using the Statistical Package for Social Sciences (SPSS) version 26, while the qualitative data was analysed using the content analysis approach. Analysed data was presented using both figures and tables. This study found a significant relationship (Î²=0.258, p=0.011) between precocious puberty and peer relationships among preadolescent girls. This was confirmed by the interview responses and the focus group narratives. The study concluded that earlier pubertal maturation led to strained peer relationships among preadolescent girls. This article recommends that forums to educate children on the stages of development and how to handle each of them be incorporated in the curriculum, to prepare girls for pubertal maturation whenever it occurs.